A survey of the availability of fish species in the landing centers of Dhi-Qar Province, Iraq, during the period from 2005 to 2016 - Nasir, N.A.; Sultan, Q.M. (Mesopotamian Journal of Marine Sciences, 2021)
The current study was designed to evaluate the landing and distribution pathways of fish in DhiQar during the period from 2005 to 2016. This investigation was carried out to overview the location of the fish landing/entering centers, the source of supply and availability of fisheries organisms in DhiQar Province. Gill net, seine net, cast net and electro-fishing gears were used mainly for catching the freshwater fish. The total fish landing in the province during the above mentioned period was about 37427 tons. The maximum landed was about 4245 tons during 2016 which accounted for about 11% of the total catch. Out of thirteen freshwater fish species, 3 were marine fish species, the total landed fish was dominated by the less economically fish such as Palaniza abu which accounted for about 44 % of the total catch. Alternatively, the highly economically fish were landed in a less amount throughout the time studied. Seven native fish species were recorded during the study which made up of 67 % of the total catch. The alien species were 3 and made about 21 % of the total fish landed. Migratory species were occurred at the lowest level and formed about 12 % of the total catch. It could be concluded that most quantities of fish landings in the fish markets has always come from the captured fisheries, the rest were coming from aquaculture production.